LINGUO CULTUROLOGICAL FEATURES OF WORDS THAT ENTERED THE UZBEK LANGUAGE FROM INDO-EUROPEAN LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article explores the linguistic and cultural characteristics of words that have entered the Uzbek language from Indo-European sources. Through an interdisciplinary approach, we analyze the historical, semantic, and sociocultural aspects of these loanwords, shedding light on the intricate process of language contact and adaptation.